Economic Aspects of Bioethanol Production - Bai, Atiila (Acta Agraria Debreceniensis, 2004)
Sustainability and multifunctionality look to be crucial points of the future of developed agriculture. Energy utilization of a part of the available biomass perfectly fits in these expectations. Bioethanol production allows for the substitution of the most expensive and most pollutable energy source, gasoline, by agricultural materials. This article contains a complex evaluation of economic characteristics of this method and calculations for the expectable economic effects of a would-be Hungarian bioethanol program. This essay includes the most important technological knowledge, a comparison between bioethanol and the competitive energy sources (gasoline, biodiesel, MTBE) and the most interesting elements of bioethanol programs operating in foreign countries. Introduced are which participants in the bioethanol chain have financial interests and counter-interests under present economic conditions in the spread of bioethanol by the enumerazation of macro- and micro-economic factors. The statements and consequences are based on my own calculatiosn so I am truly interested in any professional opinion.